Study on the Deformation and Stability of Proppant Column in High-Conductivity Channel Fracturing. (14th July 2022) - Wang, Ming; Zhang, Feng; Wang, Hanxiang
Abstract : The nonlinear constitutive model of the proppant column was established through laboratory experiments on the stability of the proppant column. Based on reservoir geomechanics and the finite element method, a fracture-proppant column interaction model was established for high-conductivity channel fracturing. The effects of in situ stress, reservoir rock elastic parameters, and spatial distribution characteristics of the proppant column on the closure deformation of the high-conductivity fracture channel and the stability of the proppant column were studied. The higher the in situ stress, the higher the contact stress on the rock plate; the lower the height and the larger the diameter of the proppant column, the more prone to deformation and breakage, while the more the effective support decreases with the increase of the in situ stress. Under the condition of constant in situ stress, with the increase of the reservoir elastic modulus, the relative axial displacement of the two slabs decreases gradually, the effective propping ratio of fractures increases, and the reservoir elastic modulus has little effect on the stability of the proppant column. The effective propping ratio decreases with the increase of the proppant column diameter, increases with the increase of the proppant column height, and increases with the increase of the ratio of the reservoir elastic modulus to in situ stress. When the proppant column diameter (proppant column spacing) is less than 3 m, the effective propped fracture ratio increases significantly. Through the above research, the optimal proppant cluster diameter was finally optimized.